Fabrication of All‐Carbon Nanotube Electronic Devices on Flexible Substrates Through CVD and Transfer Methods. (1st October 2013) - Zou, Yuan; Li, Qunqing; Liu, Junku; Jin, Yuanhao; Qian, Qingkai; Jiang, Kaili; Fan, Shoushan
<x xml:space="preserve">Abstract</x> SWNT thin films with different nanotube densities are fabricated by CVD while controlling the concentration of catalyst and growth time. Three layers of SWNT films are transferred to flexible substrates serving as electrodes and channel materials, respectively. All‐carbon nanotube TFTs with an on/off ratio as high as 105 are obtained. Inverters are fabricated on top of the flexible substrates with symmetric input/output behavior. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>